Perhitungan Dimensi Saluran Drainase Pada Daerah Persawahan Separi III dan IV Kabupaten Kutai Kartanegara - Zulfan Syahputra (Department of Architecture, Faculty of Engineering, 2017)
ABSTRACT The agricultural sector always get the attention and priority to each lamp carried out, an irrigated land needed careful planning of drainage on irrigated to prevent flooding or inundation on irrigated land.The development of irrigation network planning techniques require saluaran irrigation network which includes primary and secondary irrigation channels. The data used in planning is that the meteorological data of rainfall data, maps Contur, and data topogragrafi. The study provides the magnitude of channel dimensions trapezoidal return period of 2 years dngean dimensions W = 0.410 m, T = 2,203 m, b = 1,203 m, h = 0.746 m, while the return period of 5 years with channel dimensions W = 0.410 m, T = 2221 m, b = 1.213 m, h = 0.746 m, and when the channel dimensions 10years W = 0411 m, T = 2.232 m, b = 1.219 m, h = 0749 m.Drainage on the rice fields Separi III and IV functioned as the discharge channel rainwater runoff and excess water from the tertiary. surface drainage system open channel with trapezoidal cross-section. Trapezoidal channel shape selected for the stability of the slope of the walls can be adjusted with the material / material forming the body of the channel. Key-words : Dimension channels, primary and secondary irrigation canals, form a trapezoidal channel.ABSTRACTSector pertanian senantiasa mendapatkan perhatian dan prioritas pada setiap pelita yang dilaksanakan, suatu lahan sawah beririgasi diperlukan adanya perencanaan yang matang drainase pada sawah beririgasi untuk mencegah terjadinya banjir atau genangan pada lahan beririgasi.Pengembangan jaringan irigasi teknik memerlukan perencanaan jaringan saluaran irigasi yang meliputi saluran irigasi primer dan sekunder.Data yang digunakan dalam perencanaan adalah data meteorologi yaitu data curah hujan, peta contur, dan data topogragrafi. Hasil studi memberikan besaran dimensi saluran berbentuk trapesium kala ulang 2 tahun dngean dimensi W = 0.410 m, T = 2.203 m, b = 1.203 m, h = 0.746 m, sedangkan kala ulang 5 tahun dengan dimensi saluran W = 0.410 m, T = 2.221 m, b = 1.213 m, h = 0.746 m, dan dimensi saluran kala ulang 10 tahun W = 0.411 m, T = 2.232 m, b = 1.219 m, h = 0.749 m.Drainase pada daerah persawahan Separi III dan IV difungsikan sebagai saluran pembuang limpasan air hujan dan kelebihan air dari petak tersier.sistem drainase permukaan saluran terbuka dengan penampang trapesium. Bentuk saluran trapesium dipilih karena stabilitas kemiringan dindingnya dapat disesuaikan dengan material/bahan pembentuk tubuh saluran. Kata kunci : Dimensi saluran, saluran irigasi primer dan sekunder, bentuk saluran trapesium.